Comics, the Holocaust and Hiroshima - Chapman, Jane L. author. aut Link
VII, 95 p.
Keywords: Comics, the Holocaust and Hiroshima breaks new ground for history by exploring the relationship between comics as a cultural record, historiography, memory and trauma studies. Comics have a dual role as sources: for gauging awareness of the Holocaust and through close analysis, as testimonies and narratives of childhood emotions and experiences.